Pengelolaan Sarana dan Prasarana dalam Pembelajaran di SLB Negeri 1 Lima Kaum - Taftikhul Ummu Sa’adah; Demina Demina; Vicky Rizki Febrian; Abhanda Amra (UIN Mahmud Yunus Batusangkar, 2022)
The main problem in this thesis is that SLB Negeri 1 Lima Kaum in managing educational facilities and infrastructure has made plans but in the procurement of facilities and infrastructure it is not in accordance with the plans that have been made, there are some teachers who do not utilize the existing facilities and infrastructure optimally due to lack of ability. in operating teaching aids and learning media. The purpose of this study is to explain the management of facilities and infrastructure in learning. This research uses qualitative methods and takes place in SLB Negeri 1 Lima Kaum. Data analysis techniques used in this study are data reduction, data presentation, and conclusion drawing. The technique of checking the validity of the author's data uses several techniques, namely: triangulation and using reference materials. Based on the results of research conducted by researchers, it can be concluded that the management of facilities and infrastructure in improving the quality of learning in SLB Negeri 1 Lima Kaum includes aspects of planning, procurement, use and maintenance of facilities and infrastructure. The management of facilities and infrastructure at SLB Negeri 1 Lima Kaum has several obstacles in its implementation, such as the lack of school land, insufficient school funds, lack of learning tools, and students who do not maintain school facilities and infrastructure. This has resulted in the management of facilities and infrastructure in SLBN 1 Lima Kaum not running optimally